Peran Latar Belakang Pendidikan Orang Tua Ditinjau Dari Kualitas Belajar Peserta Didik Kelas 5 SDN 1 Pucungkidul - Kusuma Dewi, Ariana; Yasip, Yasip (Jurnal Pendidikan Tambusai, 2023)
The role of parents in children’s education is very important. Especially regarding support to achieve a good quality of children’s learning while at school. Education that has been done by parents is the basis for how parents will be able to play a role in the quality of children’s learning. As with the research at SDN 1 Pucungkidul, parents have a variety of educational backgrounds such as high school, junior high school, and undergraduate degree giving a different role to the learning quality of class V students at SDN 1 Pucungkidul. This research is a type of descriptive research using a qualitative approach, which is data relating to facts, circumstances, variables, and phenomena that occur when the research takes place and presents what it is. The subject of this research was the fifth-grade students of SDN 1 Pucung Kidul. The research instrument used observation sheets, interview sheets, and questionnaires. The results of the study show that parents with a high school educational background as caregivers play a very decisive role in children’s development. Parents with high school education are more concerned with the education of fifth-grade students at SDN 1 Pucungkidul. They will try to provide the best for their students and meet all the needs needed by students in supporting education. Teaching manners. The formation of manners starts with the family. Providing the necessities of life for parents with a high school educational background will provide sufficient learning facilities so that it influences the development of the learning quality of fifth-grade students at SDN 1 Pucungkidul. Meet school needs. Parents with a high school educational background will complete their learning tools, the more people can learn as well as possible, conversely if the tools are not complete, then this is a disturbance in the learning process, so the results will be disrupted.